Touching the World : Reference in Autobiography - Eakin, Paul John (Book collections on Project MUSE., 2001)
Paul John Eakin's earlier work Fictions in Autobiography is a key text in autobiography studies. In it he proposed that the self that finds expression in autobiography is in fundamental ways a kind of fictive construct, a fiction articulated in a fiction. In this new book Eakin turns his attention to what he sees as the defining assumption of autobiography: that the story of the self does refer to a world of biographical and historical fact. Here he shows that people write autobiography not in some private realm of the autonomous self but rather in strenuous engagement with the pressures that.